Analysis Of Demand For Indonesian Frozen Fish Exports In The Chinese Market - I made Riki Ariadi; Ilma Sarimustaqiyma Rianse; Munirwan Zani (International journal of technology and education research, 2025)
This research aims to analyse the factors influencing the demand for Indonesian frozen fish in the Chinese market. The study was conducted from November 2024 to March 2025. The data used are secondary time series data in quarterly form from 2016 to 2023, obtained through literature from relevant institutions. The analytical method employed is multiple linear regression analysis. The results show that the demand for Indonesian frozen fish exports is simultaneously influenced by China’s GDP, exchange rate, Indonesian frozen fish prices, import tariffs, and the population of China, with a significant influence of 96.6257%. Partially, the variables of Indonesian frozen fish prices and import tariffs have a positive and significant effect on the demand for Indonesian frozen fish exports in the Chinese market, while China’s GDP, exchange rate, and population have a negative and insignificant effect on the demand